The Effectiveness of Family Counseling in Reducing Juvenile Delinquency Rates - Anan, Marvina (PT. Anagata Sembagi Education, 2025)
Juvenile delinquency remains a pressing social issue that negatively impacts communities and national development. Family counseling has emerged as a crucial intervention strategy to reduce delinquent behaviors and strengthen family functioning. This study employs a systematic review of empirical research published between 2020 and 2024, analyzing 50 relevant studies on family-based interventions such as Functional Family Therapy (FFT) and Multisystemic Therapy (MST). Findings consistently show that family counseling effectively reduces juvenile delinquency and recidivism rates, although the magnitude of impact varies depending on implementation quality, cultural context, and participant characteristics. Intensive interventions with strong family engagement are associated with the most significant improvements in youth behavior and family cohesion. This study highlights the importance of integrating family counseling into prevention and rehabilitation programs, particularly in contexts where family structures play a central role in adolescent development. Future research should focus on longitudinal outcomes and cross-cultural adaptations to optimize effectiveness